Factors Affecting Organizational Success: A Case Of Body Glove - Anis Mardhiah Binti Mohd Zawawi; Daisy Mui Hung Kee; Angela Shirley Sauking; Auni Wadhiha Binti Annis; Amira Najwa Binti Amir Mustafa; Ahmad Dehrab; Neha Chandel (AIBPM Publisher, 2020)
This paper aims to investigate how Body Glove, an outdoor water sports brand started in the United States, drives organizational success. This brand specializes in wet suits. Body Glove has good product quality and continues to develop its product via research and development to meets customers’ expectations. Their passion for water sports led them to create the first wet suit to help fight those cold California waters. The price offered by Body Glove is affordable and worth it with its quality. Body Glove also provides online shopping that can ease customers to enjoy online shopping. We will test the hypotheses using survey. This paper contributes to understanding of how driving factors results in organizational success